The conjugal transfer system of Agrobacterium tumefaciens octopine-type Ti plasmids is closely related to the transfer system of an IncP plasmid and distantly related to Ti plasmid vir genes. - Alt-Mörbe, J (1996)
We have determined the DNA sequences of two unlinked regions of octopine-type Ti plasmids that contain genes required for conjugal transfer. Both regions previously were shown to contain sequences that hybridize with tra genes of the nopaline-type Ti plasmid pTiC58. One gene cluster (designated tra) contains a functional oriT site and is probably required for conjugal DNA processing, while the other gene cluster (designated trb) probably directs the synthesis of a conjugal pilus and mating pore. Most predicted Tra and Trb proteins show relatively strong sequence similarity (30 to 50% identity) to the Tra and Trb proteins of the broad-host-range IncP plasmid RP4 and show significantly weaker sequence similarity to Vir proteins found elsewhere on the Ti plasmid. An exception is found in the Ti plasmid TraA protein, which is predicted to be a bifunctional nickase-helicase that has no counterpart in IncP plasmids or among Vir proteins but has homologs in at least six other self-transmissible and mobilizable plasmids. We conclude that this Ti plasmid tra system evolved by acquiring genes from two or three different sources. A similar analysis of the Ti plasmid vir region indicates that it also evolved by appropriating genes from at least two conjugal transfer systems. The widely studied plasmid pTiA6NC previously was found to be nonconjugal and to have a 12.65-kb deletion of DNA relative to other octopine-type Ti plasmids. We show that this deletion removes the promoter-distal gene of the trb region and probably accounts for the inability of this plasmid to conjugate.